Native footprints: Photographs and stories written on the land - Martin, Kathleen J. (DigitalCommons@CalPoly, 2013)
This essay examines the work of Native photographers and artists and the ways their work addresses the decolonizing practice of the study of visual images, as well as stimulating anomalous and unexpected interpretations. It situates representations from a starting point of power, oppression and hegemony as central components of visual imagery, and also as an opportunity to promote dialogue and encourage new interpretations and narratives. This manner of investigation may function as a way to stimulate what wa Thiong’o has conceptualized as “decolonizing the mind” as it applies to images, and to re-imagine Native life as integral and continuous on this land. The goal is to present a variety of “readings” of photographs that highlight conceptions, interpretations and understandings and grapples with the enduring presence or “footprints” of Native and First Nations Peoples upon the land. Capturing and explicating footprints through images and stories may work to dispel and decolonize notions of the “vanishing Indian”. These social and contextual dimensions consider perspectives that illuminate the land we live on and the footprints we leave, not ones that historicize peoples and events as ongoing stereotypic constructions, but rather as part of an active interpreted present. Examining the work of First Nation/Native visual artists may help to unpack ideas of the hegemonic power of visual imagery that challenges representations through an array of ironic, sardonic and poignant displays.